Who framed the strip? A cross-cultural comparison of the newspaper coverage of la promenade du Portage in Hull, 1980-1995. - Dugas, Richard. (University of Ottawa (Canada), 1999)
In 1985 Hull was declared the Capital of Crime. Hull had won Quebec's unenviable title of having the highest crime rate in the province for 1984. The two dailies in the region, Le Droit (French) and The Citizen (English) closely followed the search for what was happening in the otherwise peaceful "village." The reason was simple: the concentration of bars on la promenade du Portage. The Street had been completely remodelled in the seventies by the federal government; in order to re-launch Hull's downtown core, several bars had converged on the old Main Street. La promenade's criminality and its cleanup was the subject of a large amount of newspaper articles. In this thesis I compare the ways in which the two newspapers covered the Street and the events which surrounded it. I do this at different levels: as a careful reader, through quantitative content analysis and through discourse analysis. The results show that the newspaper use very different perspectives from which to write about the same place. These perspectives help us to understand the fundamental differences in the way each community thinks the bar Strip and what it represents. The representations of this contested street inform the way the communities understand each another as well as themselves. Cultural geography is preoccupied with representations; it is through these that we learn to recognize ourselves and to recognize our place within society as well as within place. The Strip was covered in such a way as to help configure the myth that surrounds it. By using stereotypes and recurrent images, the newspapers increased the mystique and the myth of the place. In this thesis, I explore the links between place, media and representation.
Keywords: Geography.